PENERAPAN FUZZY SUGENO PADA PENILAIAN KINERJA PEGAWAI ( STUDI KASUS STMIK KAPUTAMA) - Simajuntak, Magdalena (Journal Information System Development (ISD), 2018)
Utilization of technology at this time greatly evolved along with the development of the times, so that companies or agencies require a workforce or employees who are experts in the field of technology. Employees should not only look attractive but also must have the expertise in completing the job that is given. In Higher Education must also have employees who are proficient, smart and broad-minded. Competent colleges are universities that have competent educational services not only in teaching but in the field of student administration services. In Teaching and Learning Process in Higher Education, Employees have an important role in the smooth running of lectures. For example in making Attendance List of Lectures and News Events Lectures. Improving services to students is not independent of the performance of employees. STMIK Kaputama conduct an assessment on the performance of employees through 3 (three) variables are: Expertise Variables, Variable Discipline and Attitude Variables. With parameter values: Very Low (SR), Low (R), Enough (C), Good (B) and Very Good (SB), from those parameters will be known result of Employee Performance Appraisal.